8. KNOWLEDGE OF DENGUE FEVER PREVENTION AMONG STUDENTS OF PHUC TRACH SECONDARY SCHOOL, BO TRACH DISTRICT, QUANG BINH PROVINCE IN 2022 (Vietnam Journal of Community Medicine, 2024)
Aim: The study is aimed to explore the knowledge of Dengue fever prevention and its associated factors among students of Phuc Trach secondary school in Bo Trach district, Quang Binh province in 2022.Method: This is a quantitative cross-sectional study. Data were collected from 640 students of Phuc Trach secondary school in Bo Trach district, Quang Binh province in 2022, using a self-administered structured questionnaire.Results: 93.9% of the students had adequate overall knowledge about Dengue fever prevention. However, knowledge about certain areas including the pathogen, the Dengue fever-transmitting vectors, the methods to get rid of mosquitoes and the treatment medicines was poor. Factors associated with Dengue fever prevention knowledge identified included the number of family members, the sources where students found information about Dengue fever prevention, and who provided instructions to prevent Dengue fever.Conclusion: The results highlight the importance of improving communication activities to increase knowledge about Dengue fever among school students and promote the role of schools in these activities.
Keywords: Knowledge, students, prevention, Dengue fever